Dos casas de piedra - Ravazzani, Horacio (1997)
Casa La Pirca, Punta Piedras; Uruguay. Casa La Rocosa, Laguna del Sauce; Uruguay
Keywords: VIVIENDAS EN LA COSTA; URUGUAY; VIVIENDAS UNIFAMILIARES; PIEDRA